Analytical and experimental investigation of steel friction dampers and horizontal brake pads in chevron frames under cyclic loads. (June 2022) - Kiadarbandsari, Saeed; Firoozi Nezamabadi, Maryam; Abbasi, Hassan; Yaghoobi Vayeghan, Fariborz
Abstract: Recent observations of earthquake-related damage have shown that some structural damage occurs in welded joints. Because of weak connections, the idea of using chevron bracing with a horizontal friction brake pad (FBP) damper, which can easily be replaced after an earthquake, has been proposed. First, in this study, a high-performance friction damper that can be manufactured and installed at a low cost is introduced. First, nine models were analysed numerically with ABAQUS software, and then two optimal models were selected and tested in a structural laboratory. ABAQUS software was also used to model the optimal damper inside a chevron frame and analyse its performance. In addition, three 8-story buildings were considered, one with a moment-resisting frame (MRF), one with a structural bracing system with an added damping and stiffness (ADAS) damper, and one with an FBP damper. Then, eleven far-field earthquake records were used for nonlinear time history analysis. Next, the effect of the friction damper between two adjacent buildings was investigated by modelling a 5-story structure using OpenSees software under seven earthquake records. The results show that a very high stress concentration occurs in the damper area of the brake pad after a load is applied to the bracing frame, while dampers in other elements, such as beams and columns, provide less stress. The ten-screw model has the highest energy absorption, according to parametric studies. Compared to other frames, the chevron frame with a friction damper exhibits a 32% increase in energy absorption. By analysing other seismic parameters of the frame, the damper improves frame performance